Ecosystem Services and Global Ecology (IntechOpen, 2023)
The aim of Ecosystem Services and Global Ecology is to give an overview and report from the frontiers of research of this important and interesting multidisciplinary area. Ecosystem services as a concept plays a key role in solving global environmental and human ecological crises and associated other problems, especially today when the sixth major extinction event of the history of the biosphere is in progress, and humanity can easily become a victim of it. Human activity is rapidly transforming the surface of the Earth, its biosphere, atmosphere, soil, and water resources. Ecological processes happen over a long time scale, thus damage caused by human activity will be perceptible after decades or even centuries. We hope that our book will be interesting and useful for researchers, lecturers, students, and anyone interested in this field.